C-Sections, Obesity, and Health-Care Specialization: Evidence from Mexico - Catalina Herrera-Almanza; Fernanda Marquez-Padilla; Silvia Prina (Institute of Labor Economics (IZA), 2023)
This study explores whether hospitals with higher increases in obesity levels have higher CS rates and the consequential effects on maternal and newborn health in Mexico for 2008-2015. It models how changes in the obesity level of hospitals' patient pools may affect the quantity and quality of care by focusing on the use of CS and the potential returns to specialization. And it creates a measure of hospital-level obesity, based on the fraction of obesity-related discharges for women of childbearing age. Exploiting temporal and hospital variation of this measure, results show that higher hospital-level obesity increases a woman's probability of having a CS. Also, delivery-related birth outcomes improve: maternal mortality, birth injuries, and birth trauma decrease. The evidence is consistent with hospital-level specialization in CS leading to better birth outcomes.
Keywords: I11; I18; J13; D22; 330; healthcare specialization; c-sections; obesity; maternal mortality; newborn health